(untitled) (Biological Sciences - PJSIR, 2003)
An exact axisymmetric asymptotically flat field , is deterrnined by Einstein equations, possessing a quadrupole moment due to a static mass, may be treated as a perturbation on Schwarlschild field . Exploiting this, planetary equations under the influence of the mentioned gravitational field has been worked out. The results exhibit features that shed new light on issues in relativistic celestial mechanics and models of planetary motion.